2000
DOI: 10.1111/j.1741-3737.2000.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Parenting on the Development of Adolescent Alcohol Misuse: A Six‐Wave Latent Growth Model

Abstract: Alcohol use increases throughout adolescence. Based on family socialization theory, it was hypothesized that family factors, particularly parental support and monitoring, would influence individual trajectories in the development of alcohol misuse. Six waves of data were analyzed, based on interviews with 506 adolescents in the general population of a northeastern metropolitan area. Using growth-curve longitudinal analysis, results show that parenting significantly predicts adolescents' initial drinking levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
345
5
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 409 publications
(394 citation statements)
references
References 34 publications
26
345
5
10
Order By: Relevance
“…These findings are consistent with many studies showing that early initiation of alcohol is more prevalent among White than among African American youth (e.g., Catalano et al, 1993;Johnston et al, 1987;Rachel et al, 1980). In addition, Barnes et al (2000) found that African American adolescents had lower intercepts and slopes than their White counterparts. Thus, current adolescent rates of alcohol use appear to be lower for African Americans than for White youth.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings are consistent with many studies showing that early initiation of alcohol is more prevalent among White than among African American youth (e.g., Catalano et al, 1993;Johnston et al, 1987;Rachel et al, 1980). In addition, Barnes et al (2000) found that African American adolescents had lower intercepts and slopes than their White counterparts. Thus, current adolescent rates of alcohol use appear to be lower for African Americans than for White youth.…”
Section: Discussionmentioning
confidence: 96%
“…To accurately assess changes in alcohol consumption and to determine the predictors of various developmental trajectories in youth alcohol use, it is important to conduct longitudinal studies in which the same respondents are followed over time (Barnes et al, 2000). Developmental studies have emphasized the importance of examining growth models of representative samples of youth and including sociodemographic factors such as age, gender, and race (Schulenberg et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The initial response rate was 71 percent, with black families deliberately oversampled (N = 211) in order to facilitate the testing of race-specific hypotheses. Additional data were collected, using the same procedures, in five subsequent waves ending in 1996; stringent follow-up procedures yielded retention rates of over 90 percent for each of these waves (see Barnes et al, 1997Barnes et al, , 2000 for details on sampling procedures and sample characteristics). In the present analysis, independent variables were derived from wave one of the data (1989); outcome variables were measured in wave three, approximately two years later (unweighted sample n = 612).…”
Section: Datamentioning
confidence: 99%
“…It is well established that parenting practices are related to teenage drinking (Barnes et al, 2000;Roche et al, 2008). A recent systematic review found that many different measures of positive parenting practices (i.e., increased parental monitoring and communication and positive parent-child relationship) were related to delayed alcohol initiation and reduced drinking (Ryan et al, 2010).…”
Section: Parenting Practices and Drinking And Drivingmentioning
confidence: 99%